Hasil Belajar Siswa Pada Materi Kalor Menggunakan Pembelajaran Kolaborasi Berbasis E-Learning (KABEL) - Iib Marzuqi; Ida Kaniawati; Maryani; Heny Ekawati Haryono (Postgraduate, University of Mataram, 2023)
This study aimed to determine whether student learning outcomes after using e-learning-based collaborative learning (KABEL) on heat material were better and whether there was a significant difference between student learning outcomes before and after the using KABEL application. This experimental study used a pre-experimental design and a one-group post-experimental design. Data was collected by giving a multiple-choice pre-test and post-test to 150 randomly selected class XI students. The results of data analysis showed that student learning outcomes increased by 47.34 when compared to the material before and after using e-learning-based collaborative learning. The learning outcomes of students' attitudes and skills after using e-learning-based collaborative learning (KABEL) are in the very good category, with an average score of 3.66 for the attitude aspect and 3.8 for the skills aspect.